Collective phenomena - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Quantum field theory techniques are able to describe precisely, inter alia, collective phenomena of statistical and solid state physics.Method: The path integral method with a Wick rotation shows its complete analogy with the partition function of statistical mechanics.Results: The Landau-Ginzburg phenomenology successfully describes collective phenomena such as spontaneous magnetization and superconductivity.Conclusions: Symmetry breaking phenomena could give macroscopic results.
Keywords: vacuum energy; symmetry breaking; Landau-Ginzburg model